Use of dental MRI for radiation-free guided dental implant planning: a prospective, in vivo study of accuracy and reliability - Hilgenfeld, Tim; Jürchott, Alexander; Jende, Johann; Rammelsberg, Peter; Heiland, Sabine; Bendszus, Martin; Schwindling, Franz Sebastian (European radiology, 2020)
To evaluate the accuracy and reliability of dental MRI for static guided implant surgery planning.
Gesehen am 12.08.2021